2011
DOI: 10.1037/a0025437
|View full text |Cite
|
Sign up to set email alerts
|

Motivational enhancement therapy for African American substance users: A randomized clinical trial.

Abstract: Limited empirical evidence concerning the efficacy of substance abuse treatments among African Americans reduces opportunities to evaluate and improve program efficacy. The current study, conducted as a secondary analysis of a randomized clinical trial conducted by the Clinical Trials Network of the National Institute of Drug Abuse, addressed this knowledge gap by examining the efficacy of motivational enhancement therapy (MET) compared with counseling as usual (CAU) among 194 African American adults seeking o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 63 publications
3
40
1
Order By: Relevance
“…One recent CTN study demonstrated that Real Men Are Safe (REMAS), an HIV risk-reduction intervention for substance abusing men, was less effective with Black than White male substance users (Calsyn et al, 2011). Conversely, several other CTN studies revealed that interventions with limited effectiveness for White substance users were more beneficial for one or more racial ethnic minorities (Covey et al, 2010; Montgomery, Burlew, Kosinski, & Forcehimes, 2011; Winhusen et al, 2008). …”
Section: Why Culturally Adapt?mentioning
confidence: 94%
“…One recent CTN study demonstrated that Real Men Are Safe (REMAS), an HIV risk-reduction intervention for substance abusing men, was less effective with Black than White male substance users (Calsyn et al, 2011). Conversely, several other CTN studies revealed that interventions with limited effectiveness for White substance users were more beneficial for one or more racial ethnic minorities (Covey et al, 2010; Montgomery, Burlew, Kosinski, & Forcehimes, 2011; Winhusen et al, 2008). …”
Section: Why Culturally Adapt?mentioning
confidence: 94%
“…Individuals who self-identified as Hispanic American (10.6%) or other race (5.4%) were excluded from the analyses due to the small number of participants. The demographic information and the CONSORT diagram outlining eligibility, enrollment, randomization, treatment and follow-up rates for the entire CTN 0004 sample (Ball et al, 2007) and for Black participants (Montgomery et al, 2011) are available elsewhere. The demographic information for Black and White participants in the current study is shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Milligan et al (2004) found that Black participants living in the United States completed significantly fewer days of treatment than their White counterparts. Further, Montgomery et al (2011) found that Motivational Enhancement Therapy (MET) was not effective in reducing substance use in a predominately Black cocaine-using sample. However, in another study, substance use outcomes were favorable among a predominately White cocaine-using sample participating in MET (Stein et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Montgomery, Burlew, Kosinski, and Forcehimes (2011) found that motivational enhancement therapy (MET) was not as effective in reducing substance use in a predominately African American sample as it was in reducing substance use among a predominately White adult sample participating in a multisite trial of MET conducted as part of the National Drug Abuse Treatment Clinical Trials Network (Ball et al, 2007). Field, Cochran, and Caetano (2012), comparing a brief motivational interviewing (MI) intervention to treatment as usual, also reported racial differences in outcomes among a sample of White, Black, and Hispanic individuals who screened positive for alcohol misuse.…”
Section: Introductionmentioning
confidence: 99%